The prevalence and clinical significance of a reduced ventricular ejection fraction in asymptomatic young elite endurance athletes. (11th May 2022) - De Bosscher, R; Janssens, K; Dausin, C; Goetschalckx, K; Bogaert, J; Ghekiere, O; Van De Heyning, C; Elliott, A; Sanders, P; Kalman, J; Herbots, L; Willems, R; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): National Health and Medical Research Council of Australia Background: Ventricular ejection fraction (EF) is the most widely used parameter to evaluate ventricular systolic function. Endurance athletes presenting with a reduced ventricular EF often raise the question of an underlying dilated or arrhythmogenic cardiomyopathy. The clinical significance of a reduced EF in athletes remains to be elucidated. Purpose: To investigate the prevalence and clinical significance of a reduced EF in asymptomatic endurance athletes. Methods: Two hundred eighteen asymptomatic young elite endurance athletes were evaluated at baseline. Cardiac magnetic resonance imaging (CMR) was performed to assess cardiac volumes, left ventricular and right ventricular EF (LVEF and RVEF), mass and fibrosis. Athletes with reduced EF (ATrEF) were defined as those having LVEF<50% and/or RVEF<45%. Ventricular systolic and diastolic function were assessed by trans-thoracic echocardiography. A 12-lead ECG and 24-hour holtermonitoring assessed electrical alterations and arrhythmias. In 145 athletes, LV and RV contractile reserve was evaluated by exercise CMR. Cardiopulmonary testing was performed in all athletes to measure maximal oxygen uptake (VO2max). Results: Thirty-one ATrEF (14.2%) were compared to 187 athletes with a preserved EF (ATpEF). ATrEF were more frequently males (93 vs 77% male, p=0.033) but did not differ from ATpEF with regard to age (18.8±2.1 vs 18.3±2.1 years, p=0.25). Ten athletes had an isolated reduced LVEF, 10 had an isolated reduced RVEF and 11 had both a reduced LVEF and RVEF. ATrEF had similar end-diastolic volumes and cardiac mass but differed by higher end-systolic volumes. Peak exercise LVEF and RVEF determined by exercise CMR remained lower in ATrEF (68±3 vs 73±4% and 62±6 vs 69±5%, p<0.001) but contractile reserve was greater (ΔLVEF 18±5 vs 14±4% and ΔRVEF 19±5 vs 15±5%, p<0.01). A reduced EF was not associated with lower exercise capacity, in fact VO2max was higher in ATrEF than in ATpEF (65±6 vs 62±9mL/kg/min, p=0.020) and the percentage of predicted VO2max by the Wasserman equation were similar (151±14 vs 149±21%, p=0.533). Fibrosis was present in 3 ATrEF and 18 ATpEF (9.7 vs 9.6%, p=0.993) and was isolated to the RV hinge-points in all but 3 ATpEF who had midmyocardial LV lateral wall fibrosis. LV systolic strain (-17.5±2.0 vs -19±2.1%, p<0.001) was lower in ATrEF whereas RV free wall systolic strain (-24.9±3.7 vs -25.1±3.5%, p=0.776) was similar. Diastolic function was normal in all ATrEF and ATpEF. Pathologic T-wave inversions were present in 2 ATrEF and 13 ATpEF (6.5 vs 7%, p=0.999). Ventricular premature beats (VPB) were infrequent but more prevalent in ATrEF than in ATpEF (2[0-18] vs 1[0-2]/24h, p=0.025; 16.1 vs 2.7% >100/24h, p=0.006). Conclusion: A reduced ventricular EF is common in asymptomatic young elite endurance athletes, is more frequent in males but is not associated with structural, functional or electrical abnormalities apart from a minor excess in VPB.